(untitled) - Hicks, John (Oxford, 1977)
This collection of essays on money and growth brings together the work of Sir John Hicks. Including two previously unpublished essays, this collection is sure to make readers view Hicks work in a new light.
Keywords: Economics,Money,Economic development